Influence of school absenteeism, peer influence and parental factors on students’ achievement in basic science and technology in Ibadan Metropolis (2018)
A school is a place of learning in morality and inculcating discipline in students. It is established as the agent of the society to mould the habits, interest, attitudes and feelings of children and transmit societal norms, culture, values’ and traditions from one genera/ion to another. In spite of the advantages of schooling, some students do not attend classes and the situation in the secondary schools regarding the issue of absenteeism has damaging effects on students’ academic achievement. Therefore, this study examined the impact of school absenteeism, parental factors and peer influence on the academic performance of junior secondary school basic science and technology students in Ibadan metropolis. Five research questions guided this study. The study is a survey with a population of 143,692 junior secondary school students in Ibadan metropolis from where 800 students were selected using simple random sampling technique. Three instruments used are: “Students Attendance Record” (SAR) obtained from the school register. “Parental Factor and Peer influence Questionnaire (PFPIQ), r=0.82 and “Students Achievement Test” SAT) r=0.79. Data collected was subjected to descriptive analysis of frequency counts, percentages and mean and inferential statistics using Pearson Product Moment Correlation and Multiple regression analysis at 0.05 level of significance. The result showed a significant relationship between absenteeism and students’ achievement (.r=.284*, N=1091, p. 05). There was a positive significant relationship between peer influence and students’ achievement (r = 247*, n - 1091, p<. 05), absenteeism from school, lack of positive support from parents and peer influence affects students’ academic performance. Therefore, parents should support their children and monitor their activities while strong ties should exist between the school and the home to prevent absenteeism and negative peer influence.